The Women’s Empowerment in Agriculture Index (WEAI): Results from the 2011-2012 Bangladesh Integrated Household Survey - Sraboni, Esha; Quisumbing, Agnes R.; Ahmed, Akhter (International Food Policy Research Institute, 2013)
The Women’s Empowerment in Agriculture Index (WEAI) is a new survey-based index designed to measure the empowerment, agency, and inclusion of women in the agricultural sector in an effort to identify ways to overcome those obstacles and constraints (Alkire et al. 2012). This technical report, prepared by researchers from the International Food Policy Research Institute (IFPRI), presents the WEAI, computed for the Feed the Future zone as well as rural Bangladesh as a whole.